If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -7 = 6x Reorder the terms: -7 + 9x = 6x Solving -7 + 9x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + 9x + -6x = 6x + -6x Combine like terms: 9x + -6x = 3x -7 + 3x = 6x + -6x Combine like terms: 6x + -6x = 0 -7 + 3x = 0 Add '7' to each side of the equation. -7 + 7 + 3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 0 + 7 3x = 0 + 7 Combine like terms: 0 + 7 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| 2x-7+3x=19-x | | -12+5k=10 | | n-7=35 | | 8x-20=5x-5 | | 10=x+3y | | -11i+2i= | | 2x-12=28+x | | 2(2y-5)=13 | | 6a+3a=8 | | 8b=3b+5 | | .5(x+8)=163 | | 12+z=-8 | | 1.8kg=xgrams | | 1.8kg=g | | 101+101x-x= | | -2x+4=-4x+8 | | 21y-3=10y+195 | | f=i+(i*r) | | p=0.0009*8 | | -15+y=5 | | 8-n=-3(2n-4) | | 2x-134=x+570 | | 3x-9x+6=0 | | 6a+3whena=8 | | 2x+3x-8=5x-8 | | 2-3a=8-2(2a+5) | | 5x+9y=-13 | | 1(x+5)-3x=71 | | 3+2(x+5)=11 | | -nx^2+tx+c= | | 7sinx-10cosx= | | x+26=3x+12 |